Trigeminal nerve stimulation (TNS) for children with attention deficit/hyperactivity disorder and fetal alcohol spectrum disorder: Feasibility study protocol - Joseph O’Neill; Shantanu Joshi; Jeffry R. Alger; Andrew F. Leuchter; Benjamin N. Schneider; Mary J. O’Connor (PLoS ONE, 2025)
Symptoms of attention deficit/hyperactivity disorder (ADHD) are common, severe and highly impairing in children with prenatal alcohol exposure (PAE), but often non-responsive to medication, leaving many with no good treatment. External trigeminal nerve stimulation (TNS) is a minimal risk, non-invasive neuromodulatory intervention that is FDA-cleared for ADHD. No formal trial, however, has tested TNS in children with known PAE. We present here the protocol of the first clinical trial of TNS in children with ADHD associated with PAE. The study also uses multimodal MRI to explore possible brain mechanisms of TNS. An open-label pilot will be conducted of 4 weeks of TNS in 30 youth with ADHD associated with PAE, recruited in Southern California. Children will receive TNS nightly for 4 weeks. Safety, tolerability, and preliminary efficacy will be evaluated. Efficacy outcomes include change in the investigator-administered parent-rated ADHD Rating Scale and the Clinical Global Impression Improvement (CGI-I) score for ADHD. Effects on executive function, mood, and sleep are also assessed. Maintenance of effects is evaluated at 4-week follow-up. TNS-related brain changes and predictors of response are measured using structural MRI, diffusion tensor imaging (DTI), magnetic resonance spectroscopy (MRS), and resting-state fMRI before and after treatment. This study will determine whether TNS is feasible in children with ADHD and PAE, whether it improves clinical and cognition symptoms, and whether efficacy persists 4 weeks. Trial registration: clinicaltrials.gov (NCT06847165) and protocol ID: IRB-24–0648-AM-007 June 16, 2025.